EFEKTIVITAS MODEL CONTEXTUAL TEACHING AND LEARNING DALAM MENINGKATKAN HASIL BELAJAR AQIDAH SISWA KELAS VII MTS MUHAMMADIYAH 3 MASARAN - Muslim, Latifah Nisa’i Yan; Nashir, Muhammad Ja’far (Jurnal Manajemen Pendidikan, 2025)
This study examined the effectiveness of implementing the Contextual Teaching and Learning (CTL) model on seventh-grade students’ Aqidah learning outcomes at MTs Muhammadiyah 3 Masaran in the 2024/2025 academic year. Methods: A quantitative pre-experimental approach with a one-group pretest–posttest design was applied to 36 students. Data were gathered using a 20-item objective Aqidah test (pretest and posttest) and a 20-item Likert questionnaire measuring CTL implementation. The questionnaire showed good internal consistency (Cronbach’s alpha = 0.872). Data normality was assessed using Shapiro–Wilk and differences were tested using a paired-samples t-test. CTL implementation was perceived at medium-to-high levels. Pretest and posttest scores were normally distributed (p=0.075; p=0.081). The mean score increased from 81.00 to 91.14. After the intervention, 75% of students were in the high achievement category and none were in the low category. The paired t-test indicated a significant improvement (t=-7.533, p<0.001, df=35) with a mean gain of 10.14 points and a 95% confidence interval of [-12.871, -7.407]. CTL strengthens engagement through inquiry, collaborative learning, faith-based modeling, reflection, and authentic assessment. By linking doctrinal concepts with everyday situations, students can develop more meaningful understanding and internalize Aqidah values beyond rote memorization.